TAILORING LOCAL CULTURAL NORMS IN THE TEACHING OF ENGLISH - Rusdi Rusdi (Universitas Negeri Padang, 2015)
It is generally accepted that the main function of language is as an instrument tbr expressing thoughts and culture. Therefore, it is argued that. rvhen Indonesian speakers are communicatin-e in English- they will communicate reflecting Indonesian cultural norms and values. They are not expected to communicate in English using English native speakers' cultural norms and values. In line r.vith this argument. English as an international lan-euage is understood as diversities reflecting different cultural norms of people coming from ethnicities when they communicate in English. It is alsoiargued that English teaching should be based on local cultural norms and values. The local cultural norms',ttrd values themselves need to be identified and mapped for teaching purposes. Besides, Students should also be taught to be arvare of the existence of cultural differences when communicating in English lvith people from different ethnicities. This article also reviews cultural dimensions and patterns of communication of people from 'East' and 'West'.